Shooting the Messenger? Supply and Demand in Markets for Willful Ignorance - Shaul Shalvi; Ivan Soraperra; Joël J. van der Weele; Marie-Claire Villeval (Tinbergen Institute, 2019)
We investigate the role of advisers in the transmission of ethically relevant information, a critical aspect of executive decision making in organizations. In our laboratory experiment, advisers are informed about the negative externalities associated with the decision-maker's choices and compete with other advisers. We find that advisers suppress about a quarter of "inconvenient'' information. Suppression is not strategic, but based on the advisers' own preferences in the ethical dilemma. On the demand side, a substantial minority of decision makers avoid advisers who transmit inconvenient information (they "shoot the messenger''). Overall, by facilitating assortative matching, a competitive market for advisers efficiently caters to the demand for both information and information avoidance. Decision-makers are less likely to implement their preferred option when they are randomly matched to advisers and there is no scope for assortative matching.
Keywords: D91; C91; D83; D82; 330; Self-deception; information avoidance; unethical behavior; experiment